A Studying of The Qur'an Annisa' Verse 3 Regarding The Phenomenon Of Paid Polygamy Mentoring: STUDYING OF THE QUR'AN ANNISA' VERSE 3 REGARDING THE PHENOMENON OF PAID POLYGAMY MENTORING Irma Nur Hayati, Fauzan Zenrif Student in The Islamic University of Malik Maulana Ibrahim Malang, Malang Indoneisa1 Lecture in The Islamic University of Malik Maulana Ibrahim Malang, Indonesia Lecture in The Islamic University of Malik Maulana Ibrahim Malang, Indonesia - Irma Nur Hayati Hayati; Fauzan Zenrif Zenrif (el-Bait: Jurnal Hukum Keluarga Islam, 2022)
Abstract: This paper tries to reveal another side of the phenomenon of violence against women which is currently viral on social media. It is related to the case of paid polygamy mentoring which is not in accordance with Islamic law and the conditions of Indonesian society in particular. The glorification of women's violence is a frightening threat to marriages that can start with polygamy. In the sense of violence, Polygamy has implication for the concept of gender, both in terms of gender, physical, sexuality, and psychological differences.In fact, the scholars explained in the Qur'an, namely, "Shalihun likulli zammani wa makkani." It means that the Qur'an emphasizes that women's justice in marriage is appreciated contextually, namely monogamy. The aim of this paper is analyzing of the Qur'an on Annisa’ Verse 3 on women’s violence glorification in paid polygamy mentoring campaigns. It is used the Maudhu'i interpretation method. Thus, there is an effort to reform the style (uslub) of Islamic da'wah without the need to explore the law in length and width which has implications on the grammatical side, which is also able to prevent the emergence of ideological contradictions of contemporary thought.In conclusion, polygamy may be carried out as long as it is carried out with the correct Shari'ah and Islamic law and is not due to customary factors, or local environmental traditions, and does not burden one party.